Literasi Sebagai Strategi Evaluasi Kurikulum Merdeka Untuk Mencerdaskan Praktik Pembelajaran Bahasa Indonesia di SMA Terpadu Raudhatul Ulum Pidie Jaya - Nurfitri, Nurfitri (LaKaspia, 2024)
This study, entitled “Literacy as an Evaluation Strategy of the Merdeka Curriculum to Enhance the Practice of Indonesian Language Learning at SMA Terpadu Raudhatul Ulum Pidie Jaya,” aims to examine the role of literacy as an evaluation strategy in improving the quality of the Merdeka Curriculum implementation. Literacy in this context is not limited to the ability to read and write but serves as an evaluative approach that measures students’ critical, creative, and analytical thinking skills. This research employed a qualitative method with a case study design involving teachers and students through in-depth interviews, classroom observations, and curriculum document analysis. The findings reveal that literacy-based evaluation positively impacts student engagement and comprehension of learning materials. This strategy enables teachers to obtain a more comprehensive understanding of students’ abilities, as the assessment focuses not only on cognitive aspects but also on reflective and applicative skills. However, the implementation of literacy-based evaluation still faces challenges, such as limited teacher competence in designing literacy assessment instruments and insufficient supporting learning resources. Therefore, continuous teacher training and institutional support are needed to effectively integrate literacy into the evaluation process. This research is expected to provide both conceptual and practical contributions to the development of literacy-based evaluation strategies that enhance the effectiveness and intelligence of Indonesian language learning practices within the Merdeka Curriculum framework.